Herramienta de evaluación técnico-táctica en pádel - Fernández de Ossó Fuentes, A. I.; Leon-Prados, J. A. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
The analysis of Technical-Tactical performance Indicators (TTPI) is a usual topic on sports studies because they predetermine the performance and allow to establish the extent that defines the course of the game. In this work, we intend to design and validate an instrument that measures TTPI in professionals and amateur paddle players.